Purification and characterization of an agglutinin from datura innoxia with antineoplastic activity - Singh, Ruby; Nawale, Laxman; Gaikwad, Sushama M.; Suresha, C. G. (National Science Day, At CSIR-NCL, 2015)
Lectins are carbohydrate binding proteins of non-immune origin. Due to their multivalency, lectins can be easily detected using agglutination. Lectins are reported to induce cytotoxicity or inhibition of growth in various cancer cells., hence good therapeutic startegy against cancer. Factors such as specificity, stability, assay rapidity, and costs combine to make lectins attractive diagnostic reagents. Datura innoxia belongs to family of Solanaceae.All parts of the plant are hallucinogenic, hypnotic and narcotic. Application: at low dose acts as pain killer, relieves asthma and rheumatism.